IMPLEMENTASI KEBIJAKAN PEMUNGUTAN RETRIBUSI PELAYANAN PARKIR DI PASAR INDUK KOTA AMUNTAI KABUPATEN HULU SUNGAI UTARA - Reno Affrian (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2016)
A parking service at a special parking place gets a retribution charged to the users of vehicles who parked at the top of the buildings, at parking lots on streets/ parking areas, buildings and/or parking equipments. One of the special parking places in Kabupaten Hulu Sungai Utara is the central market of Amuntai City since there is an increase in the volume of motor vehicles and mobility of people and vehicles that carry out activities in the central market of Amuntai city, then it allows an increase of local revenues (PAD) from parking services every year. Based on the research result that local regulation had not been implemented according to the regulations. It can be seen from the management of a special parking place cooperated with the third party. There was no clear procedure for determining the location of special parking places, and the parking management was monopolized by the parking manager, so that in practice the local regulation was ineffective and inefficient, especially if it was aimed at supporting local revenues without considering the optimization of the real local revenue (PAD). The factors influencing, were communication, resources. disposition and bureaucratic structure.